COLLABORATIVE GOVERNANCE IN PUBLIC COMPLAINT SERVICES: EXAMINING THE SUCCESS OF PRO DENPASAR - I Gusti Ayu Nindya Astari; Ni Wayan Widhiasthini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the implementation of collaborative governance in the Pelayanan Rakyat Online (PRO) Denpasar system, focusing on how multi-actor collaboration contributes to the effectiveness of public complaint management. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation, and analyzed using the collaborative governance framework of Ansell and Gash. The findings indicate that the collaborative process in PRO Denpasar generally aligns with the theoretical framework, as reflected in clear institutional arrangements, strong leadership support, and adaptive interaction among stakeholders. The system is further strengthened by a structured digital platform, standardized procedures, defined response time, and adequate human resources, which collectively enhance responsiveness and accountability in handling public complaints. However, the study also reveals that collaboration remains largely government-centered, with the government acting as the dominant actor. The involvement of the private sector is still limited to technical and situational roles, while academic participation is minimal or absent. In addition, several challenges persist, including fragmented complaint channels, limited technical features such as mapping integration, and suboptimal community participation influenced by concerns over personal data security. Despite these limitations, PRO Denpasar demonstrates a transition toward data-driven governance and increased public engagement. The study concludes that strengthening collaborative governance requires expanding stakeholder involvement, particularly by fostering strategic partnerships with the private sector, integrating academic contributions for evidence-based policy development, improving system integration, and enhancing public trust through effective communication and data protection measures.